Branch and bound with simplicial partitions for global optimization - Žilinskas, Julius (Mathematical Modelling and Analysis, 2008)
Branch and bound methods for global optimization are considered in this paper. Advantages and disadvantages of simplicial partitions for branch and bound are shown. A new general combinatorial approach for vertex triangulation of hyper‐rectangular feasible regions is presented. Simplicial partitions may be used to vertex triangulate feasible regions of non rectangular shape defined by linear inequality constraints. Linear inequality constraints may be used to avoid symmetries in optimization problems. First Published Online: 14 Oct 2010